INTELLECTUALS AND NEW RIGHT IN ARGENTINA: EXPERTS, MEDIA AND IDEOLOGISTS IN THE PRO CONSTITUTION - Pulleiro, Adrián Pulleiro (Revista de Historia Social y de las Mentalidades, 2019)
In the framework of the Argentine crisis of 2001-2002, PRO emerged, a new political formation that in 2007 reached the City Hall of the City of Buenos Aires and in 2015 it conquered the central government. The objective of this article is to investigate the role played in the process of emergency and consolidation of the PRO by a group of intellectuals who worked in "advisory" tasks and in certain think thanks. We analyze actions and discourses produced within concrete historical experiences that cross political practices, institutional dynamics and intellectual trajectories. We prioritize the 2007-2015 period, since it marks the consolidation phase of the PRO and allows us to notice changes in the role and functioning of the practices and spaces that we are interested in investigating.
Keywords: Intellectuals; Culture; Politics; New Right